Send in the Crowds: Planning and Benefiting from Large-scale Academic Library Events - Michelle Demeter; Rachel Besara; Gloria Colvin; Bridgett Birmingham (Marketing Libraries Journal, 2018)
Academic libraries produce a range of events. While large-scale events can be a lot of fun, the planning process can seem more daunting than the process for programming that targets smaller audiences. Planning and executing large-scale events—ones that attract one hundred or more attendees, involve partners, and meet the social and academic needs of students—can be very worthwhile in terms of marketing the library and networking. In this article, the authors detail four different events that can be replicated in an effort to show how easy and beneficial large-scale events can be within the academic library community.